Variations in the annual cycle of the East Asian monsoon and its phase-induced interseasonal rainfall anomalies in China - Song JIANG; Congwen ZHU; Ning JIANG (Atmospheric and Oceanic Science Letters, 2020)
The East Asian monsoon (EAM) exhibits a robust annual cycle with significant interannual variability. Here, the authors find that the EAM annual cycle can be decomposed into the equinoctial and solstitial modes in the combined sea level pressure, 850-hPa low-level wind, and rainfall fields. The solstitial mode shows a zonal pressure contrast between the continental thermal low and the western Pacific subtropical high, reaching its peak in July and dominating the East Asian summer monsoon. The equinoctial mode shows an approximate zonal contrast between the low-level cyclone over the east of the Tibetan Plateau and the western Pacific anticyclone over the east of the Philippines. It prevails during the spring rainy season in South China and reaches its peak in April. The interannual variations of the lead–lag phase of the two modes may result in the negative correlation of rainfall anomalies in North China between spring and fall and in South China between winter and summer, which provides a potential basis for the across-seasonal prediction of rainfall. The warm phase of ENSO in winter could give rise to the reverse interseasonal rainfall anomalies in South China, while the SST anomaly in the Northwest Pacific Ocean may regulate the rainfall anomaly in North China.